59.7k views
1 vote
AlCl3 + NaOH —> Al(OH)3 + NaCl

1 Answer

1 vote

Hey there!

AlCl₃ + NaOH → Al(OH)₃ + NaCl

Balance OH.

1 on the left, 3 on the right. Add a coefficient of 3 in front of NaOH.

AlCl₃ + 3NaOH → Al(OH)₃ + NaCl

Balance Cl.

3 on the left, 1 on the right. Add a coefficient of 3 in front of NaCl.

AlCl₃ + 3NaOH → Al(OH)₃ + 3NaCl

Balance Na.

3 on the left, 3 on the right. Already balanced.

Balance Al.

1 on the left, 1 on the right. Already balanced.

Our final balanced equation: AlCl₃ + 3NaOH → Al(OH)₃ + 3NaCl

Hope this helps!

User Abhishek Ranjan
by
5.5k points